Entrepreneurial Deliberateness of Youth of Karnali Province - K.C., Govinda (Journal of Entrepreneurship & Management Studies, 2024)
Any nation’s overall development is based on careful consideration and in-depth development of each subsector of the local, regional, and national economies. An economy’s ability to grow and develop is greatly influenced by entrepreneurship. This study employs the theory of planned behavior (TPB) as a framework. The variables of PA (Personal Attitude), PBC (Perceived Behavioral Control) and SN (Subjective Norms) are heavily weighted in this study. The study’s foundation is a quantitative research paradigm. Utilizing a structured questionnaire, data were gathered. The youth of the Karnali Province who are presently enrolled in Birendranagar Surkhet to pursue higher education make up the study’s population. Regarding this research, the convenience sampling method was employed. The study’s practical implications center on a trend that policymakers should watch going forward: teach young people in the Karnali province the skills they need to get information from the market about starting a business, expand their access to financing, and improve the viability of their business ideas.